ダイ12ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1971 - 中西, 秀二; ナカニシ, シュウジ; 福井, 徹郎; フクイ, テツロウ; 村松, 照男; ムラマツ, テルオ; NAKANISHI, Syuji; FUKUI, Tetsuro; MURAMATSU, Teruo (国立極地研究所, 1974)
P(論文) This paper describes the results of surface and aerological weather observations at Syowa Station between 1 February 1971 and 5 February 1972. Most of the methods and instruments are the same as in 1970; a meteorological satellite tracking system to receive the pictures was installed. Some meteorological characters of this period were: Temperature and solar radiation were lower than the average; Bad weather were experienced from February to April and from August to November; Snow accumulation was greater than the average; Temperatures of all the upper layers in winter were lower than the average. Total amount of ozone was observed on every suitable day except the polar night season. departmental bulletin paper